'An old and faithful servand': A Pair of Early Seventeenth-Century Gauntlet Gloves given by King Charles I to Sir Henry Wardlaw. (January 2015) - Robinson, Claire
<x content-type="archive" xml:space="preserve">Abstract</x> A pair of embroidered seventeenth-century gauntlet gloves, reputedly presented by King Charles I to his courtier Sir Henry Wardlaw, was donated to the University of St Andrews in 2001. This article sets out to uncover the truth behind this nearly four-hundred-year-old family legend by investigating Sir Henry's royal connections and the social significance of the gauntlet gloves as a high-status, luxury clothing accessory. Based on the study of historic gloves in museum and private collections, it endeavours to date the gloves by discussing their design and manufacture within the context of seventeenth-century clothing fashion. This article also explores the symbolism behind the gauntlet gloves' decorative scheme by unravelling some of the hidden messages that are conveyed about cultural, religious, political and technological developments and perspectives through seventeenth-century embroidery.